Woman, marriage and motherhood: issues of Private International Law from a gender perspective - Vaquero López, Carmen (CUADERNOS DE DERECHO TRANSNACIONAL, 2018)
In the latest times, the fight for achieving the gender equality and for putting an end to the injustices that separates men and women has become a true “revolution” that has invaded practically all social areas. This movement should also remove the principles that inform the solutions of International Private Law. In this paper we analyze from a perspective of gender two institutions that have traditionally been a bastion of patriarchy and whose regulation has been carried out from mainly androcentric considerations: the marriage and the motherhood.